The Severity of the Pathophysiology, Specificity, and Clinical Course of Chronic Liver Diseases, Particularly Chronic Hepatitis - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Biomedicine and Pharmacy, 2025)
For many years, chronic liver diseases have been one of the main and urgent problems of the fields of Gastroenterology and Hepatology. In particular, statistical indicators show that in the last 20 years, the incidence of liver diseases in the population has increased significantly. In a single case, statistics obtained on the scale of the CIS countries show that as a result of observations conducted in the population for 12 months, from 500 to 1,000,000 people were registered liver diseases caused by damage to the liver by various etiological factors. Unfortunately, to date, about 2 billion residents on Earth suffer from liver diseases. From year to year, the reason for the increased damage to liver cells is the increased diversity of etiological factors. In particular, with the damage of liver cells to medicamentosis, viral, toxic, alcohol and autoimmune, 2-3 million inhabitants are being registered every year. For this reason, we can cite the fact that most drug preparations are metabolized in the liver, that carbohydrates, proteins, fats are metabolized in the liver, and that the liver plays an important role in external and internal disintoxication.